Synthesis and Characterization of Graphene Oxide-Modified Bi2WO6 and Its Use as Photocatalyst - Xiaoyue Hu; Xiangchao Meng; Zisheng Zhang (International Journal of Photoenergy)
A Bi2WO6 photocatalyst modified with graphene was synthesized in a two-step template-free hydrothermal process. The prepared samples were characterized to explore their properties. The photocatalytic activities of the prepared samples were investigated by degrading dye model, Rhodamine B (RhB), under visible light irradiation. This showed that the modified Bi2WO6 photocatalyst with 1.2 wt% of graphene greatly improved photocatalytic activity during the degradation of dye pollutants, compared to pure Bi2WO6. The enhancement can be interpreted as the integrated effects of ultrahigh charge carriers’ mobility and high adsorption of RhB on graphene. Additionally, effects including catalysts dosage amount, pH of RhB solution, and temperature of reactor on the photocatalytically degrading RhB were also studied and discussed.